ANALIS MODEL PEMBELAJARAN EFEKTIF DALAM IMPLEMENTASI DEEP LEARNING DI KURIKULUM SEKOLAH - Mutmainah, Siti; maulidiyah, Syfa; Mafrikha Fauziah, Alda; Amrullah, Muhamad Agung; Ana, Nurlaila (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The low quality of rote-learning-based instruction is a significant problem at various levels of education in Indonesia. This study aims to analyze effective learning models for implementing deep learning in school curricula through a literature review approach. The method used is a literature study analyzing national and international journal articles published between 2021 and 2026, obtained through Google Scholar, Garuda, and DOAJ. The results of the study indicate that Project-Based Learning, Problem-Based Learning, and Inquiry-Based Learning models have proven effective in supporting the implementation of deep learning. The three main pillars—meaningful learning, mindful learning, and joyful learning—have been shown to holistically enhance students’ critical thinking skills and conceptual understanding. In conclusion, the integration of deep learning into the school curriculum can be an effective strategy for improving the quality of learning if supported by adequate teacher readiness and policies.